(untitled) (E Global Congress, 2024)
In the article, the author examines in detail the role of banks and money in digital transformation. The legal documents in the Republic of Uzbekistan regarding the transition of the domestic economy to a digital form were studied. The author also assessed the impact of the COVID-19 pandemic on the state of the global economy, including the digital one. The history of the transformation of banking services, the advantages and disadvantages of digital banks were also studied by the author of this article.